(untitled) - Gregory, Kristiana (New York, 2001)
In her diary, a young girl writes about her life and the events surrounding the beginning of the American Revolution in Philadelphia in 1776.
Keywords: Diaries; Fiction; Revolution, 1775-1783; Fiction; History; Fiction; United States; Revolution, 1775-1783; History; Fiction; Philadelphia (Pa.); Revolution, 1775-1783; History; Philadelphia (Pa.); Fiction; Revolution, 1775-1783